Paper No 8.3: Nanoimprinted Organic Electrochemical Transistors. (September 2013) - Rothländer, T.; Gold, H.; Haase, A.; Jakopic, G.; Hartmann, P.; Stadlober, B.; Hütter, P. C.
Abstract: The use of organic molecular and polymer materials in circuitry has received considerable attention during the last years. These multifunctional materials enable the low‐cost production of simple designed organic electronic devices and logic circuits that are driven at low voltages. We report on electrochemical transistors (ECTs) structured by nanoimprint lithography (NIL). With this technique it is possible to fabricate transistors with critical dimensions in the sub‐micrometer regime, which should lead to higher switching speed and improved overall transistor performance.